Root Distribution and Nitrogen Fixation Activity of Tropical Forage Legume American Jointvetch (Aeschynomene americana L.) cv. Glenn under Waterlogging Conditions - Manabu Tobisa; Masataka Shimojo; Yasuhisa Masuda (International Journal of Agronomy)
We investigated the root distribution and nitrogen fixation activity of American jointvetch (Aeschynomene americana L.) cv. Glenn, under waterlogging treatment. The plants were grown in pots under three different treatments: no waterlogging (control), 30 days of waterlogging (experiment 1), and 40 days of waterlogging (experiment 2). The plants were subjected to the treatments on day 14 after germination. Root dry matter (DM) weight distribution of waterlogged plants was shallower than controls after day 20 of waterlogging. Throughout the study period, the total root DM weight in waterlogged plants was similar to that in the controls. Enhanced rooting (adventitious roots) and nodule formation at the stem base were observed in waterlogged plants after day 20 of waterlogging. The average DM weight of individual nodules on the region of the stem between the soil surface and water surface of waterlogged plants was similar to that of individual taproot nodules in the controls. Waterlogged plants had slightly greater plant DM weight than the controls after 40 days of treatment. The total nitrogenase activity (TNA) of nodules and nodule DM weight were higher in waterlogged plants than in the controls. Waterlogged American jointvetch had roots with nodules both around the soil surface and in the area between the soil surface and water surface after 20 days of waterlogging, and they maintained high nitrogenase activity and net assimilation rate that resulted in an increased growth rate.